Determination of the virulence of single nucleopolyhedrovirus occlusion bodies using a novel laser capture microdissection method. (7th December 2020) - Munsamy, Thrishantha; Bouwer, Gustav
Abstract : Determination of the virulence of occlusion bodies (OBs), which are the horizontal transmission structures of nucleopolyhedroviruses (NPVs), is an important area of baculovirology. A method for inoculating an insect with an isolated OB was developed using Helicoverpa armigera nucleopolyhedrovirus (HearNPV) infection of second instar Helicoverpa armigera larvae as a model NPV–host pathosystem. In this novel method, laser capture microdissection (LCM) was used to directly catapult single OBs onto the surface of insect diet in bioassay containers. Since exposure via the natural oral horizontal transmission route of each larva to a single OB was established and not subject to chance variation, the method facilitated determination of the insect mortality rate (4.8%) associated with exposure to single HearNPV OBs. Droplet feeding bioassays confirmed that the novel method did not reduce OB virulence. The LCM method sets a foundation for virulence and genetic diversity studies based on single NPV OBs.